Teacher perceptions of effectiveness of a mathematics teacher professional development programme - Sojen, Jaya (My University, 2020)
South African learners face serious deficits in mathematics learning at the schooling level. Low learner performance is more pronounced in the case of low-quintile schools. Several factors have been reported to contribute to low learner performance in mathematics. One of them is teacher quality. Because teachers are the only support for learning for learners from disadvantaged socio-economic backgrounds, it is imperative that teacher quality is improved in order to improve learner achievement in low-quintile schools. Eventhough several mathematics teacher professional development programmes have been implemented in South Africa to improve teacher quality, small-scale qualitative studies, in the form of classroom observation and perception studies, report that these teacher professional development programmes lack in quality and focus on content, and that they are delinked from the classroom context, thereby lacking effectiveness. The purpose of this research was to evaluate one such mathematics teacher professional development programme, the Mathematics Teacher Professional Development Programme (MTPDP), implemented in six schools in Ivory Park in the Gauteng Province. This study intended to explore the teachers’ perceptions of the effectiveness of the MTPDP through capturing the teacher experiences of participation in the MTPDP vis-à-vis exploring the teachers’ perceptions of the effectiveness of the design attributes of the MTPDP, the new knowledge acquired of content and pedagogy and the change in teachers’ classroom practice. The conceptual framework proposed by Desimone (2009) for evaluating the effectiveness of teacher professional development programmes informed the conceptual framework used in this study. Desimone’s (2009) framework presents an action model akin to a theory of change model (Boylan, Coldwell, Maxwell, & Jordan, 2018) to evaluate the impact of teacher professional development programmes in bringing about improved learner outcomes. The critical design attributes of a professional development programme enable positive teacher experiences of participation, thereby enabling teacher acquisition of knowledge and by extension a change in teachers’ classroom practice (Desimone, 2009). This leads to impacting positively on teacher instruction and thereby improving the learner outcomes (Desimone, 2009). Thus, the model represents a connection between critical features of professional development, teacher knowledge acquisition, change in classroom practice and learner outcomes as a continuum of change for evaluating the effectiveness of a teacher professional development programme. This research pursued a qualitative approach with an interpretivist case study design. A sample of eight teachers was interviewed using semi-structured interviews. The thematic analysis highlighted that the teachers perceived the effectiveness of MTPDP as enabling teacher learning, enhancing teacher knowledge, improving teacher self-efficacy and bringing about transformation in teachers’ classroom practice from a predominantly teacher-centred practice to a learner-centred practice. Broad design features of the MTPDP, namely the content-based workshops and the classroom-based component of MTPDP were perceived as effective and found strong resonance among the teachers. The design attributes of ‘coherence’, ‘content coverage’, ‘active learning’, ‘sharing ideas and teacher collaboration’, ‘modelling classroom delivery’ and ‘monitoring classroom implementation’ were perceived as effective by the teachers in enabling learning. The acquisition of ‘knowledge of introducing subject matter’ and ‘knowledge of multiple strategies’ were perceived as effective in enhancing teacher knowledge. The acquisition of ‘knowledge of multiple strategies’ garnered the maximum buy-in from the teachers and was perceived by them as the sustainable feature of the MTPDP. The acquisition of knowledge enabled by these features of the MTPDP in a safe learning environment was perceived as effective by teachers leading to improved teacher perception of self-efficacy, leading to a transformation in teachers’ classroom practice from a predominantly teacher-centred practice to a learner-centred practice. Thus, the teachers’ overall perceptions of effectiveness of the MTPDP along the continuum of change informed by the conceptual framework of Desimone (2009) was positive. Though the teachers perceived the MTPDP as effective, the effectiveness would have been only at a superficial level as the low content knowledge of teachers may hinder new teacher beliefs from wholly manifesting in classroom practice.
A thesis presented in partial fulfilment for the degree of Master in Management to the Faculty of Commerce, Law and Management, University of Witwatersrand, 2020
Keywords: UCTD; Teacher perceptions; Mathematics teacher; Professional development programme; South African learners; Mathematics Teacher Professional Development Programme; SDG-4: Quality education